Promise not to tell [compact disc, unabridged] - Krentz, Jayne Ann (Recorded Books, 2018)
After one of her artists sends her a painting before apparently taking her own life, Seattle gallery owner Virginia teams with private investigator Cabot Sutter to catch the true killer and uncover the truth about the cult they were a part of as children.